AIDS symptoms in America: Close-ups from the underground. Issue 1 (1st August 2021) - Ferrari, Anna
After the explosion of the AIDS epidemic in the United States was virtually ignored because it was mostly hitting the gay community, gay authors started to employ their work for two main purposes: to protest the situation and, particularly in the beginning, to spread information about the virus. The portrayal of physical details is one of the most interesting devices employed in AIDS texts. In the early AIDS years, when the cause of the epidemic was unknown, literary tools such as the list of symptoms were widely used: authors were addressing their own community, and gave people a way to recognize the early signs of illness, such as the night sweats and the Kaposi's sarcoma lesions. Even after the discovery of HIV, when there was not a cure yet, AIDS texts represented a crucial source of information: the first official leaflet was provided by Surgeon General Koop in 1986. The act of incorporating medical information in literary texts was considered an act of service within the community: authors such as Paul Monette and Larry Kramer regarded the gay underground as a more credible source of information, since in the beginning people who had gotten through it often knew more than the doctors. Later on, as information became more available, the display of those same physical manifestations of the disease and of AIDS-ridden bodies became an effective way to denounce the persisting silence from the government, with works such as Kushner's Angels in America and Wojnarowicz's portraits of Peter Hujar's body. This article focuses on how the display of symptoms and other physical manifestations of the epidemic turned the cultural production into a key element in shaping the discourse around AIDS, highlighting the evolution in the use of physical medical evidence ‐ from information to outcry.